Familial Depressive Symptoms and Delinquency: Separate Self-Reports From Mothers and Their Offspring - Ellis, Lee (International journal of offender therapy and comparative criminology, 2018)
Research has documented that both unipolar and bipolar depression are positively correlated with involvement in delinquency and crime. The present study sought to broaden the understanding of these relationships by looking for links between offending and family histories of depressive symptoms in relationship to offspring delinquency. More than 6,000 college students and their mothers provided self-reported information regarding feelings of depression. Students provided self-reports of involvement in various categories of offending and drug use from ages 10 through 18. Numerous significant positive correlations were found between general feelings of depression and of manic depression and involvement in delinquency. The depression-delinquency relationships were strongest when considering offspring themselves, although maternal depression symptoms were also associated with various forms of offspring delinquency and drug use. To help assess the causal chains that might be involved, multiple regression and mediation analysis revealed that parental depression enhanced the probability of offspring feeling depressed and may have thereby contributed to offspring being delinquent, particularly in the case of manic depression. This study reconfirmed the well-established relationship between depression and involvement in delinquency and drug use, and suggests that it extends back to parental forms of depression, especially by the mother.